Towards telehealth delivery in pediatric rheumatology practice - Raju Khubchandani; Tadej Avčin; Angelo Ravelli (BMC, 2023)
Abstract Introduction Much has been written and spoken about telemedicine since about two decades including an article in this journal at the start of the pandemic. It took a global catastrophe to enforce its usage across the world in various medical specialties. Telemedicine however remains unstructured, unregulated and lacks uniformity. Discussion This article highlights the practical learnings and opinions of the authors who provided over two thousand video consults and asynchronous telemedicine services through the entire pandemic. It includes lessons learnt from emerging economies where pediatric rheumatologists are scarce. Pediatric rheumatology, which relies heavily on history, musculoskeletal and skin examination is aptly suited to exploit telemedicine in its synchronous and asynchronous forms. Pediatric tele rheumatology could temporarily address the shortage and uneven distribution of specialists in vast parts of the globe, besides serving as a method of triage and shared care with the primary physician. Reduction of direct and indirect costs and family/primary physician education are additional benefits. There also exist challenges for all stakeholders and it is important to address the latter. Conclusion The learnings of the pandemic suggest a vital role for telemedicine in the practice of pediatric rheumatology. This is a fertile area for research and consensus building by international and national pediatric societies and issue position statements like some adult bodies already have. The authors speculate a hybrid system of care in the not-so-distant future.